Implementasi Sistem Load Balance dengan Metode PCC Untuk Optimalisasi Pada Jaringan Internet Local - Sujatmika, Arif Rahman; Abidin, Ahmad Anas; Winarti, W (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The need for the internet at this time is very high and is no longer the beginning to be used, even the internet has become a mandatory thing for humans to support various needs such as looking for information, knowledge articles, learning media and looking for vacations, based on the need for internet can causing connection traffic on the internet and the load on the server will also increase and to overcome very slow internet performance it is necessary to use more than one ISP on this system the method used to combine two or more lene ISP requires configuration of the PCC method (Per Connection Classifier) this method it is very helpful to overcome slow connections to provide the conclusion of the PCC (Per Connection Classifier) method with the results of the 192Mbps throughput measurement in the very good category, the 1% packet loss results in the very good category, from the 30ms delay measurement results in the very good category and from gauge an 1ms jitter is in the very good category.